A Correlation Between Knowledge and Dietary Patterns With the Incidence of Anemia Among Pregnant Women in The Working Area of Penarik Health Center 2025 - Andri Yunita; Nimas Ayu Lestari Nurjanah; Ice Rakizah Syafrie (Multidisciplinary Journals, 2026)
Anemia in pregnant women remains a public health problem that can have adverse effects on both the mother and the fetus, especially in the second and third trimesters when iron requirements increase. Factors that play a role in the occurrence of anemia include the level of knowledge and dietary patterns of pregnant women. This study aimed to determine the relationship between knowledge and dietary patterns and the occurrence of anemia in pregnant women in the second and third trimesters in the working area of Penarik Health Center in 2025. This study used an analytical observational design with a cross-sectional approach. The population in this study was all pregnant women in the second and third trimesters in the working area of Penarik Health Center, with a sample size of 45 respondents taken using purposive sampling technique. Data were collected through questionnaires to measure knowledge and dietary patterns, as well as hemoglobin level examination to determine the occurrence of anemia. Data analysis was carried out univariately and bivariately using the Chi-Square test. The results showed that the majority of respondents had sufficient knowledge (40.0%), good dietary patterns (57.8%), and did not experience anemia (53.3%). Bivariate analysis results showed a significant relationship between knowledge and the occurrence of anemia in pregnant women in the second and third trimesters (p < 0.000), and there was a significant relationship between dietary patterns and the occurrence of anemia (p = 0.008). The conclusion of this study is that there is a meaningful relationship between knowledge and dietary patterns and the occurrence of anemia in pregnant women in the second and third trimesters in the working area of Penarik Health Center. It is expected that health workers can increase health education and nutrition counseling for pregnant women as an effort to prevent anemia during pregnancy.